Basic reproduction number for certain infectious porcine diseases: estimation of required level of vaccination or depopulation of susceptible animals - V. M. Gulenkin; F. I. Korennoy; A. K. Karaulov (Ветеринария сегодня)
Basic reproduction number (R0) is one of the fundamental quantitative characteristics in epidemiology of infectious human and animal diseases. This parameter reflects the biological properties of the infectious agent, the social and economic aspects of animal husbandry, natural factors associated with the habitat of the animal population invaded by the virus (microorganism), as well as the effectiveness of methods selected for infection control, in particular, the implementation of preventive measures; it also allows foreseeing the number and probability of occurrence of new secondary outbreaks in the area at risk of the disease spread. The paper presents data on the estimation of basic reproduction number (R0) for a range of infectious porcine diseases. A systematic analysis has been undertaken with respect to the publications available on the estimation of R 0 for various virus isolates of African swine fever, classical swine fever, foot-and-mouth disease, porcine reproductive and respiratory syndrome, Aujeszky’s disease, hepatitis E, encephalomyocarditis, porcine circovirus type 2, as well as pleuropneumonia associated with Actinobacillus pleuropneumoniae, and diseases caused by pathogenic isolates of Mycoplasma hyopneumoniae. Based on the obtained R0 values, recommendations for the veterinary services are made on preventive vaccination of pigs against the above mentioned diseases in the areas at risk of infection spread. The necessary conditions for wild boar depopulation aimed to prevent new African swine fever outbreaks are identified, namely, the elimination of at least 75% of the wild boar population living in the risk zone within the period of time equal to one infectious period.